A 2-tier architecture to support real-time communication in CSMA-based networks - Ricardo Moraes (2008)
The main objective of this thesis' is to address the following question: "How to guarantee the timing requirements of real-time (RT) control data, when the communication medium is shared with timing unconstrained traffic?". That is, to propose mechanisms that enable the support of RT communication services in CSMA-based communication infrastructures, specifically when such infrastructures are also being used to support multipurpose data transfer applications. The target is to address the timing requirements of typical industrial applications. Thus, a new RT-communication approach (VTP-CSMA) has been proposed, which is based on the use of traffic separation mechanisms. Such mechanisms are able to prioritize RT-traffic over multipurpose traffic, without directly controlling the latter. That is, instead of controlling all the traffic generated by all the stations, this approach controls only the traffic generated by the RT stations. The VTP-CSMA approach forces the collision resolution in favor of the RT stations, enabling the fulfillment of the RT communication requirements.